DESIGN AND IMPLEMENTATION OF A WEB-BASED E-REPORTING APPLICATION FOR SENIOR HIGH SCHOOL EDUCATION KEY PERFORMANCE INDICATORS IN LOCAL GOVERNMENT ENVIRONTMENT - Endra Abdul Hadi; Davit Hermawan; Raden Deden Ahmad Hidayat; Nurdiansyah Permana (Journal of Multimedia Technology and Applied Software, 2025)
The rapid advancement of information technology has driven digital transformation across various sectors, including education. The Garut District Education Office requires an effective information system to manage educational indicator data for Senior High Schools (SMA). This research aims to design and develop a web-based e-reporting application to automate the reporting process of secondary education Key Performance Indicators (KPIs). The system development methodology employs the waterfall model with an object-oriented approach. The application was developed using PHP, MySQL, and modern web technologies. The research findings demonstrate that the e-reporting application successfully addresses the problem of manual work accumulation, accelerates the reporting process, and generates accurate information for educational policy decision-making